Alkyl Sulfinates: Formal Nucleophiles for Synthesizing TosMIC Analogs - Lujan-Montelongo, J. Armando (European J Org Chem, 2015)
Alkyl sulfinates function as formal nucleophiles in Mannich-type reactions to give sulfonyl formamides, which are readily dehydrated to the corresponding sulfonylmethyl isonitriles. The efficient, two-step synthesis provides a general route to sulfonylmethyl isonitriles from readily available methyl sulfinates or thiols. Mechanistic analysis reveals that the unusual nucleophlicity of the alkyl sulfinates arises from the in situ release of sulfinic acids.